Reconfiguration of Radial Distribution Systems: An Efficient Mathematical Model - Mahdavi, Meisam [UNESP] (2021)
For a few decades, researchers try to reach a better solution by proposing new models or methods for distribution system reconfiguration (DSR) problem. This paper presents an efficient model for reconfiguration of radial distribution systems, aiming loss minimization. The proposed model can be easily solved by every commercial solvers and software. The proposed mixed-integer second-order cone programming (MISOCP) model was tested on 16-, 33-, 69-, 70-, 119-, and 136-bus test systems as well as Taiwan power company network (TPC). The results show high efficiency of the proposed model for reconfiguration of radial distribution systems.